Analytical validation of 39 clinical chemistry tests and 17 immunoassays on the Alinity analytical system. (2nd May 2022) - Lapić, Ivana; Šegulja, Dragana; Dukić, Kristina; Bogić, Anamarija; Lončar Vrančić, Ana; Komljenović, Sven; Šparakl, Tajana; Grdiša Teodorović, Katarina; Cigula Kurajica, Vlasta; Baršić Lapić, Ivana; Kralik Oguić, Saša; Kozmar, Ana; et al.
Abstract: The aim of this study was to perform the analytical validation of Alinity c and i analyzers (Abbott Laboratories, Chicago, IL, USA) for 39 clinical chemistry tests and 17 immunoassays. Precision was evaluated at least at two concentration levels for 5 days in quintuplicate, following CLSI EP15-A3. Method comparison included parallel analysis of leftover routine samples on Alinity analyzers and the previously used Cobas c501 and e601 (Roche Diagnostics, Mannheim, Germany). Linearity was tested by preparing sequential sample dilutions with high analyte concentration, following the CLSI EP6 document. For clinical chemistry tests, within-run coefficients of variation (CV) were up to 6.0% (beta-2-microglobulin), while between-run CVs up to 5.4% (immunoglobulin M). Among immunoassays, the highest within-run CV was obtained for vitamin B12 (6.9%), while between-run for CA 19-9 (4.3%). Complete agreement with Roche analyzers was observed for 16 (41%) clinical chemistry assays and 6 (35%) immunoassays. Half of all evaluated assays did not meet the desirable biological variation criteria for bias, being especially exceeded for alpha1-antitrypsin, apolipoprotein A1, ceruloplasmin, complement C3 and C4, hemoglobin A1c, lipoprotein (a) and myoglobin, as well as some tumor markers (CA 125, CEA, fPSA, AFP, and ferritin), hormones (cortisol, DHEA-S, insulin) and vitamins (25-OHD). Linearity in the tested ranges was confirmed. Overall, this study revealed that precision criteria derived from manufacturer's claims were not satisfied for all assays while comparison study for some assays yielded differences that imply the need for additional assay evaluation prior to introduction into routine practice.